Teaching young musicians to play expressively through movement in the orchestra classroom - Young, Katherine (Kansas State University, 2022)
Over the past few years of teaching, I have realized that there are many pedagogical elements to consider when teaching students to perform with musical expression. One of those considerations is the movement of the body while playing. Students will perform a series of steps to produce a more musical tone and better musical expression through bodily movement. Movement will focus on unilateral and bilateral movement of the upper body in relation to the individual’s bow direction. The lessons outlined in my report will demonstrate how to introduce expressive movement through simple open-string exercises and scales. Students will eventually apply these movements to their repertoire. When exploring the topic of movement while playing, I realized, as an educator, you cannot leave anything to chance. Expectations for students learning need to be defined by what the educator can and is willing to introduce, not what the students might learn on their own. If something is important to know, then the educator must incorporate it into their teaching. During my coursework, I became aware that playing practices I thought came naturally to musicians were not always so. Through teaching four grade levels, it was always curious to me why some students were so stoic in their playing by the time they entered 8th grade. At some point, I became aware that moving in music does not come naturally to most students. Then I came to my second realization: I am the one who encouraged these stoic movements from the onset. I had overemphasized posture and form. I realized that my students were trying to emulate perfect playing posture, which made them very rigid. I forgot to teach them to move within the confines of good posture. I also have made the mistake of not incorporating movement early enough. It is my conclusion that all students can be taught to play expressively through movement of the body.
Keywords: Teaching musicians to play expressively; Orchestra